The Preliminary Ruling Decision in the Case of Google vs. Louis Vuitton Concerning the AdWord Service and its Impact on the Community Law - Tomáš Gongol (Amfiteatru Economic Journal, 2013)
The internet user after entering the keywords obtains two kinds of search results – natural and sponsored ones. The following paper deals with the issue of using keywords which correspond to trademarks registered by a third party for advertising purposes through internet search portals such as Google, Yahoo, Bing, Seznam, Centrum etc. (in principle web search portals). The objective of this article is to analyze decided cases dealing with the AdWords service issued by the Court of Justice of the European Union and compare them also with the attitude in similar disputes in the U.S. Within this knowledge it is necessary to determine the impact of these decisions on further national courts decisions of European Union member states. Moreover there is also legal impact on copyright law and responsibility of internet search engines deduced. The method of the analysis of courts decisions is used and the method of legal comparison is applied to different attitudes in similar cases. Where a third party uses a sign which is identical with the trademark in relation to goods or services identical with those for which the mark is registered, the trademark proprietor is allowed to prohibit such use if it is liable to affect one of the functions of the mark (particularly the function of indicating origin). Regarding to the liability of the Internet search engine itself, decisions of the courts in matters of Internet search engines in the European Union vary from state to state. Whereas the German courts tend to currently access the responsibility for the outcome of the search engines more freely, the French courts are often more stringent. Differently, we can say much more liberal, is the access of the U.S. courts to this issue. Preliminary ruling decision in case of Louis Vuitton Malletier SA vs. Google, Inc. and community practice in further cases follow similar (liberal) decisions of the courts of the U.S.
Keywords: K29; 330; keyword advertising; Google Adwords; Louis Vuitton; preliminary ruling decision; protection of consumer; search portal; trademark protection